Long-term effects of a combination of isoflavones, agnus castus and magnolia extracts on climacteric symptoms and cardiometabolic risk profile in postmenopausal women. (3rd April 2022) - Maffei, Silvia; Franchini, Michela; Fortunato, Loredana; Guiducci, Letizia
Abstract: Objective: To evaluate the long-term effects of a combination of isoflavones, agnus castus and magnolia extracts (combined isoflavone compound [CIC]) on climacteric symptoms and cardiometabolic risk in symptomatic postmenopausal women. Methods: This interventional, prospective study evaluated climacteric symptoms, mood and sleep disorders using the 21-item Greene Climacteric Scale (GCS) and 7-item Insomnia Severity Index (ISI) questionnaires; and cardiovascular, metabolic and thrombotic risk markers at baseline (T0) and after 12 months of CIC treatment (T1). Results: In healthy postmenopausal women ( N  = 71), 12-month CIC treatment significantly reduced patient-reported vasomotor symptoms (100% vs. 17%), mood disorders (67% vs . 25%) and sleep disorders (89% vs. 19%%) (all p  < .001) compared with baseline; and significantly improved GCS psychological, somatic, and vasomotor domain scores and ISI sleep disturbance scores (all p  < .05). CIC significantly reduced systolic ( p  = .022) and diastolic blood pressure ( p  < .001), and heart rate ( p  < .001); glucose concentrations ( p  = .018), HOMA index ( p  = .013), and ALT ( p  = .035), homocysteine ( p  = .005) and NT-proBNP ( p  = .003) levels. Conclusions: Long-term CIC therapy improved vasomotor symptoms, mood disorders, sleep disorders, hemodynamic measurements and cardiometabolic risk markers in healthy postmenopausal women. ClinicalTrials.gov Identifier: NCT03699150.